Paddy fiber as an alternative sustainable acoustic absorber material - Yasseer, Abdullah (2014)
The use of synthetic materials as acoustic absorbers is still applied extensively in building industry. These non-biodegradable materials do not only cause pollution to the environment but also contribute significantly in increasing the CO2 causing the effect of global warming. Therefore researchers have now driven their attentions to find sustainable and eco-friendly materials to be an alternative sound absorber. This study discusses the use of natural waste fibers from dried paddy as fibrous acoustic material. Since this is one of common natural waste materials found across South East Asia, the usage will also minimize the production cost. Samples of sound absorbers from paddy fibers were fabricated and the acoustic properties were determined through experiment. The paddy fibers are found to have good acoustic performance with normal incidence absorption coefficient greater than 0.5 from 1 kHz and can reach the average value of 0.8 above 2.5 kHz. The sound absorption performance can be further increased at lower frequency range by 50% with a layer of polyester cloth added to its front surface. The absorption coefficient result from sample with weight of 3 grams and thickness of 20 mm is found to be comparable against that from the commercial synthetic glass wool.